Signal quality comparison of customer base and branching methods in fiber to the home network design - Rahayu, Yusnita; Azhary, Muhammad Raihan; Ngah, Razali; Ali, Arbiansyah (Universitas Mercu Buana, 2025)
One communication medium that is well-known for its outstanding and reliable performance is fiber optic. A social example of its application is the Fiber to the Home (FTTH) network. The goal of this study is to evaluate the signal quality of the customer base method and the branching method, two FTTH-building techniques based on the PT.PLN Icon Plus standards, in order to identify the most practical approach for use in the Air Hitam 2 cluster. Two scenarios were used in this study at the Fiber Access Terminal (FAT) with 1:16 and 1:8 splitters. The fiber optic cable path design findings demonstrate that the branching approach is a wise decision, utilizing optical fiber cables for a total of 9 Km, with the greatest cable distance being 2.5 Km from the Optical Line Terminal (OLT) to the end FAT. According to theory, in the 1:16 splitter situation and the 1:8 splitter scenario, the optical power received by the Optical Network Terminal (ONT) is -19.13 dBm and -16.03 dBm, respectively, with an OLT transmit power of 3 dBm. For these cases, the simulation results are -17.98 dBm and -20.27 dBm. Additionally, the budget value for the rising time reaches 0.253 ns. The bit error rate values in the 1:16 and 1:8 splitter scenarios are 3.157 × 10-10, and 1.63507 × 10-28, respectively, while the Q factor values are 6.18233 and 11.014, respectively. Based on theory and simulation, these findings suggest that the branching strategy can deliver good performance.